Identification of the immune-associated enhancer RNA SATB1-AS1 as a novel biomarker for thymic cancer prognosis - Hongpeng Wang; Yichu Huang; Guangtao Min; Lei Jiang (PLoS ONE, 2025)
Objective To screen key enhancer RNAs (eRNAs) in thymoma (THYM) through The Cancer Genome Atlas (TCGA) database and explore their potential as prognostic molecules and therapeutic targets in THYM. Methods Gene expression RNA-seq profiles of 33 cancer types were retrieved and downloaded from the TCGA database, and Kaplan–Meier survival analysis and Spearman correlation analysis were applied to screen eRNAs and target genes associated with survival in THYM patients. The correlation of target eRNAs with clinical features was assessed. Gene set enrichment analysis was performed to investigate the potential biological functions of target eRNAs. Finally, the prognostic potential of the eRNA was validated in other cancer types. Results In THYM, SATB1-AS1 and the target gene SATB1 high expression were associated with a positive patient prognosis, and SATB1-AS1 expression was negatively correlated with patient stage ( P < 0.05). Gene and pathway enrichment analyses revealed that SATB1-AS1 was associated with leukocyte transendothelial migration, natural killer cell-mediated cytotoxicity, neutrophil extracellular trap formation, PD-L1 expression and the PD-1 checkpoint pathway in cancer. Conclusion SATB1-AS1 may be a key eRNA in THYM and has the potential to be a marker and therapeutic target for the early diagnosis and prognosis of THYM.